2020
DOI: 10.1021/acs.jchemed.0c00136
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Chemical Safety Awareness and Practices in Nigerian Schools

Abstract: Chemical safety, a practice of protecting humans and the environment in which they work and live from the deleterious effects of chemical substances, was investigated in this study in Nigerian secondary schools. Using a mixed-method survey, we investigated the awareness level and implementation of the best practices of chemical safety by 1246 senior secondary school chemistry students. Students in rural schools were found to have a lower level of awareness of chemical safety compared to the students in urban s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 7 publications
2
13
0
Order By: Relevance
“…A study conducted previously , ranked chemistry concepts in the new chemistry curriculum for secondary schools in Nigeria and Ghana in order of difficulty from the most perceived difficult concept to the least perceived difficult concept. We surveyed 1292 participants from Nigeria and Ghana because both countries use the same chemistry syllabus for senior school certificate examinations.…”
Section: Why Nuclear Chemistry?mentioning
confidence: 99%
See 1 more Smart Citation
“…A study conducted previously , ranked chemistry concepts in the new chemistry curriculum for secondary schools in Nigeria and Ghana in order of difficulty from the most perceived difficult concept to the least perceived difficult concept. We surveyed 1292 participants from Nigeria and Ghana because both countries use the same chemistry syllabus for senior school certificate examinations.…”
Section: Why Nuclear Chemistry?mentioning
confidence: 99%
“…In a study previously conducted, they found that teacher sufficiency deficits for delivering online education, low internet service, erratic power supply, and severe shortcomings in infrastructure in schools are some of the factors affecting learning. An on-the-spot evaluation of the state of chemistry laboratories conducted by the authors of ref , in their study, found that a typical chemistry laboratory was thinly resourced with a few reagents in ill-labeled bottles. The preparatory room and store in 83% of the laboratories had glassware and reagents, especially acids, bases, and salts, inappropriately arranged.…”
Section: Introductionmentioning
confidence: 99%
“…32 Peter et al also studied the chemical safety awareness and best practices of 1247 secondary school students in urban and rural Nigerian schools and found that rural area students have lower levels of chemical safety awareness compared to their urban counterparts. 33 These reports necessitate the need to provide adequate training to promote safety, including handling of chemicals and disposal of waste to students and staff in all geographic locations. Menard et al presented several examples focusing on safety culture, safety attitude, safety behavior, safety training, factors contributing to laboratory accident in academia and industry from past 10 years.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Despite these efforts in the chemical sciences, including the fact that many laboratory courses have been converted to online due to the COVID-19 pandemic, recent literature reports involving laboratory incidents and poor safety culture attitudes. For example, Artdej has investigated the safety study survey of 27 fourth year undergraduate students enrolled in chemistry laboratory courses and found that most students misunderstood the meaning of hazardous chemicals and faced difficulties in matching the safety signs . Peter et al also studied the chemical safety awareness and best practices of 1247 secondary school students in urban and rural Nigerian schools and found that rural area students have lower levels of chemical safety awareness compared to their urban counterparts . These reports necessitate the need to provide adequate training to promote safety, including handling of chemicals and disposal of waste to students and staff in all geographic locations.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the students do not know what must/must not be done during laboratory studies, and they have already expressed this view in the previous question. Okebukola et al (2020) investigated the awareness level and implementation of the best practices of chemical safety by senior secondary school chemistry students in Nigerian. Students in rural schools were found to have a lower level of awareness of chemical safety than the students in urban schools.…”
Section: Secondary School Students' Views On Laboratory Safetymentioning
confidence: 99%